Subject Files of Elizabeth Teague
The series contains Elizabeth Teague's correspondence with leading experts on the USSR and Russian dissidents living abroad, which is connected to scholarly publications, organisation of conferences and participation in seminars. It contains also Teague's hand-written notes from lectures on the Soviet Union, her drafts and own articles on a particular subject or reference request, copies of articles and books relating to the topics researched, news agency releases and newspaper clippings, photographs and cartoons. Reflecting Ms Teague's professional interests, the series comprises extensive information on the Communist Party in the USSR, discipline, property, reform, unofficial groups, unemployment, etc. Of particular value are her reflections on a given topic and their discussion in numerous letters with renown Kremlinologists. Accruals not expected